2014
DOI: 10.12934/jkpmhn.2014.23.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Protective Factors for Internet Game Addiction in Middle School Students using Data Mining Decision Tree Analysis

Abstract: Purpose: This study was done to identify protective factors which predict internet game addition in middle school students using data mining decision tree analysis. Methods: The participants were 557 (Male=233, Female=324) middle school students from G city. Data were collected using structured questionnaires from March, 25 to May, 4, 2013, and analyzed using the descriptive analysis, t-test, ANOVA, decision tree, using SPSS 20.0 program. Results: The result of this research showed the prediction model for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…There are several difficulties in properly diagnosing and treating IGD. While the number of publications related to 'internet game addiction', 3 4 5 'internet game dependency', 6 7 8 'IGD', 2 9 10 11 12 13 14 and other names 11 14 has been steadily on the rise, the consensus on the standards of IGD has not yet been reached. Therefore, concept of IGD needs to be clarified further and standardized criteria for research has to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…There are several difficulties in properly diagnosing and treating IGD. While the number of publications related to 'internet game addiction', 3 4 5 'internet game dependency', 6 7 8 'IGD', 2 9 10 11 12 13 14 and other names 11 14 has been steadily on the rise, the consensus on the standards of IGD has not yet been reached. Therefore, concept of IGD needs to be clarified further and standardized criteria for research has to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents from families with better family functioning, such as more positive family physical health, belief systems, coping styles, and parent-child interaction, tend to have lower levels of addiction and are less severely addicted to gaming (Chiu et al, 2004). Although adolescents from these families may play video games to maintain current peer relationships and build new ones (Chappell et al, 2006), their high connectedness to school, characterized by satisfactory school life, conforming to school norms, and good relationships with teachers, may attenuate their gaming addiction (Kweon & Kim, 2014). Young (2009) suggested parents ask: "Is a child turning to online games because they are not doing well at school?…”
mentioning
confidence: 99%
“…Whereas increased parental control in childhood is reported to reduce the risk of IGD in adolescence, children of neglecting or uninterested families and those not communicating adequately with their children have a higher risk of IGD (Lee & Morgan, 2018). Kweon & Kim (2014) argue that family support and, especially, father attitude is a protective factor from IGD, which was more effective on boys. In particular, the quality of time spent with school-age children and parents can be protective of IGD.…”
Section: Discussionmentioning
confidence: 95%
“…Our results showed that gaming time differed between school terms, weekends, and year-end holidays and more than two thirds of the children played fewer than 2 hours a day during school terms, but this rate decreased to fewer than half during holiday periods, and in each case, the scores of those gaming more than 2 hours a day were higher. Gaming duration is an important factor associated with IGD and low self-control, and/or self-regulation ability may be effective in increased game duration; thus, it is recommended to control it (Kweon & Kim, 2014; Paulus et al, 2018). However, adopting a restriction approach before or after the problem occurs is controversial; the effect could decrease as the child grows up (Lee & Morgan, 2018), and it may even increase gaming time as a reaction (Schneider et al, 2017).…”
Section: Discussionmentioning
confidence: 99%